Surgical Management of Thoracic Osteomyelitis due to Escherichia Coli Sepsis. (27th August 2020) - Lyons, Mark K.; Kalani, Maziyar; Neal, Matthew T.; Patel, Naresh P.
Abstract : Case Report . Escherichia coli is a rare cause of vertebral osteomyelitis. It is more common in adults and males. We present a case of an immunocompetent adult male presenting with a several month history of progressive systemic symptoms and subsequent neurologic compromise. We discuss the neurosurgical evaluation of a patient with a progressive vertebral osteomyelitis and treatment options. Surgical debridement and spinal stabilization were performed and confirmed the diagnosis. The patient successfully completed a prolonged antimicrobial therapy course. The patient made a complete neurologic recovery. We discuss the presentation of a patient with Escherichia coli vertebral osteomyelitis and the successful surgical management.